PENINGKATAN KEMAMPUAN SAINS ANAK USIA 5-6 TAHUN MELALUI PERCOBAAN SEDERHANA PENCAMPURAN WARNA DI TK ISLAM DAUD KHOLIFATULLOH KOTA PADANG - Evi Desmariani; Muzayyanah; Lisa Yuniarti; Laila Rahmadona (LP2M Universitas Adzkia, 2021)
This research is motivated by the problem that the child has not been able to do simple scientific experiments and the child is still unable to recognize cause and effect about the environment. This study aims to improve the science skills of children aged 5-6 years through a simple experiment of mixing colors at the Daud Kholifatulloh Islamic Kindergarten in Padang. This type of research is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of 3 meetings. While the data analysis technique uses a percentage formula and uses a frequency distribution table. The research procedure starts from planning, implementing, observing and reflecting. The results of each cycle showed an increase in the child's ability to do simple scientific experiments and recognize cause and effect about the surrounding environment through a simple experiment of mixing colors at Daud Kholifatulloh Islamic Kindergarten, Padang. Through a simple experiment of mixing colors in conducting simple scientific experiments in pre-action 0% increased in cycle I to 30% and increased again in cycle II to 80%. Meanwhile, in recognizing the cause and effect of the surrounding environment in pre-action, 0% increased in the first cycle to 40% and increased again in the second cycle to 90%. So it can be concluded that a simple experiment of mixing colors can improve the scientific skills of children aged 5-6 years at Daud Kholifatulloh Islamic Kindergarten, Padang.